2018
DOI: 10.1007/s00264-018-4070-0
|View full text |Cite
|
Sign up to set email alerts
|

Short to midterm outcomes of one hundred and seventy one MoPyC radial head prostheses: meta-analysis

Abstract: Short- to midterm outcomes of MoPyC prostheses are satisfactory and complications associated are low. The use of stem auto-expansion as a mode of obtaining primary fixation in radial head arthroplasty appears to be an effective solution for reducing the risk of painful loosening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 51 publications
0
3
0
1
Order By: Relevance
“…Osteolysis below the neck of a radial head implant has only been investigated in a handful of studies. Laumonerie et al found osteolysis around the neck of the implant in 33% of patients after implantation of the MopYc prosthesis [29]. The authors performed a meta-analysis, reporting on a total of 171 patients, and explained the high rate of proximal loosening with the auto-expanding mechanism of the pressfit implant, leading to stress shielding.…”
Section: Discussionmentioning
confidence: 99%
“…Osteolysis below the neck of a radial head implant has only been investigated in a handful of studies. Laumonerie et al found osteolysis around the neck of the implant in 33% of patients after implantation of the MopYc prosthesis [29]. The authors performed a meta-analysis, reporting on a total of 171 patients, and explained the high rate of proximal loosening with the auto-expanding mechanism of the pressfit implant, leading to stress shielding.…”
Section: Discussionmentioning
confidence: 99%
“…The mean flexion-extension arc is described with 124.7°, the mean pronation is described with 77.0°, and supination is described with 76.8°. 16 For the Evolve ® prosthesis, in the study by Laflamme et al was described an average Mayo Elbow Performance Index (MEPI) of 97, with 1 out of 100 points for 21 patients and a follow-up period of 10.4 (2.0 -15.1) years. The revision rate of 0% is lower than in group 1.…”
Section: Discussionmentioning
confidence: 99%
“…In the meantime, however, some second-generation prostheses have established themselves and in some cases they have achieved very good results. [11][12][13][14][15][16][17] The aim of this study was to evaluate two of the prosthesis models that are used by the present authors with regards to their clinical and functional outcomes in acute care.…”
Section: Introductionmentioning
confidence: 99%
“…In der chronisch symptomatischen Situation bietet der prothetische Ersatz des Radiuskopfes eine Therapiemöglichkeit. Trotz zuverlässiger Ergebnisse der Radiuskopfprothetik, wie in mehreren Studien nachgewiesen werden konnte [2,3], sind auch spezifische Komplikationen bekannt. Eine schwerwiegende Komplikation ist die Fehlimplantation der Prothese, sodass ein sog.…”
unclassified